Pre-feasibility study of a Caribbean inward investment office (Coopers & Lybrand [S.l.], 1998)
Considers some of the problems facing the individual Caribbean countries and territories in competing for inward investment issues associated with establishing a Caribbean Inward Investment Office.
DC